A novel framework of building operation algorithm for the block of technical diagnostics of aircraft’s automatic control system - Vuong, Trung A.; Tran, Dong LT.; Vo, Thanh C.; Nguyen, Minh T.; Tran, Hoang T. (Institute of Advanced Engineering and Science, 2024)
This article presents the problem of designing an automatic control system that is stable against errors and failures of sensors on aircraft. The sensor system has a technical diagnostic block that ensures diagnosis and eliminates typical errors and failures. Based on the determination of the error vector, damage can occur by adding measurement elements corresponding to the measurement parameters to the control system. When there are errors or failures of the sensor elements, the state vector of the system changes and is determined by measurements. The difference between the measured vector components when there are errors, failures and when working normally is the basis of the working algorithm of the failure diagnosis block. The results demonstrate encouraging prospects for practical implementations.